2013
DOI: 10.4103/0970-1591.120091
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous management of renal caliceal diverticular stones: Ten-year experience of a tertiary care center with different techniques to deal with diverticula after stone extraction

Abstract: Introduction:Caliceal diverticulae are a frequent surgical problem. We present our experience with caliceal diverticular stones (CDS) managed with percutaneous nephrolithotomy (PCNL) and describe the two different techniques to deal with diverticula after stone retrieval.Materials and Methods:We retrospectively analyzed 10-year data of 44 consecutive patients who underwent PCNL for CDS. During PCNL, if the guide wire could be negoted through the neck of the diverticula, we dilated and stented it. If we couldno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Surgical time for PCNL-treated calyceal diverticula was similar to previous reports. [5171926] Time for FURS in this study was similar to that reported by Sejiny et al . [2] (80–210 min, average 91 min), however, diverticular orifices in their study were in an open state, which enabled identification of the orifices.…”
Section: Discussionsupporting
confidence: 90%
“…Surgical time for PCNL-treated calyceal diverticula was similar to previous reports. [5171926] Time for FURS in this study was similar to that reported by Sejiny et al . [2] (80–210 min, average 91 min), however, diverticular orifices in their study were in an open state, which enabled identification of the orifices.…”
Section: Discussionsupporting
confidence: 90%
“…[17] Review 4 221 PCNL Srivastava et al. [18] Retrospective 3b 44 PCNL Gücük and Üyetürk [19] Review 4 259 PCNL Zhang et al. [20] Meta-analysis 1a 2142 PCNL Siev et al.…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…PCNL remains effective in the management of upper-pole diverticula but carries the risk of pulmonary complications. In another study, it was reported that among management options for CDS, the most versatile approach with maximum stone-free and symptom-free rates is PCNL [18] . In this study, the stone clearance was more than 90% and the conclusion was that PCNL can clear calculi from calyceal diverticula in most cases with minimal morbidity.…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cases are very delicate. 12,13 The author's usual approach has been to start with a nephrostogram, so as to opacify the diverticulum and collecting system. However the diverticulum is targeted, an 18-gauge needle is used for puncture, because the needle has some directability once the tip is in the diverticulum and because of its stiffness it will not buckle in the tract.…”
Section: Calyceal Diverticulamentioning
confidence: 99%